2020
DOI: 10.7759/cureus.7729
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome of Acute Intussusception in Children Under Two Years of Age: A Prospective Cohort Study

Abstract: Background Intussusception is a common cause of small intestinal obstruction in children under two years of age. Late diagnosis can lead to a potentially worse condition. This prospective study aims to describe the clinical manifestation and develop a conservative management protocol for acute ileocaecal intussusception in children under two years of age. Methods This prospective study was carried out in 118 consecutive patients under two years of age. Patients presented with symptoms and signs of acute intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
0
5
2
Order By: Relevance
“…This finding is comparable with the findings of Jimma University Medical Center ( 22 ), Tanzania ( 21 ) and systematic reviews in African countries ( 23 ). However, it was higher than the findings of studies from South Korea ( 24 ), Latin America ( 16 ), Vietnam ( 4 ), South Africa ( 7 ), Nigeria ( 25 ), and Bahrain ( 26 ). The possible reason for this discrepancy may be attributed to the huge variations in medical infrastructure accessible for the population and the quality of health care, coupled with the unavailability of recommended modern interventions for the management of acute intussusception.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This finding is comparable with the findings of Jimma University Medical Center ( 22 ), Tanzania ( 21 ) and systematic reviews in African countries ( 23 ). However, it was higher than the findings of studies from South Korea ( 24 ), Latin America ( 16 ), Vietnam ( 4 ), South Africa ( 7 ), Nigeria ( 25 ), and Bahrain ( 26 ). The possible reason for this discrepancy may be attributed to the huge variations in medical infrastructure accessible for the population and the quality of health care, coupled with the unavailability of recommended modern interventions for the management of acute intussusception.…”
Section: Discussioncontrasting
confidence: 58%
“…Approximately 74 intussusceptions occur annually per 100,000 infants worldwide ( 2 ). It was first described in 1674 in the younger population, it may be caused by unknown aetiology in 75% of cases ( 3 , 4 ). However, 25% of cases might be caused by underlying conditions such as Meckel's diverticulum, polyp, rheumatoid purpura, and lymphoma ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms and signs for childhood intussusception are vomiting, abdominal pain, abdominal mass, and blood mixed stools, and it occurs in various proportions. 3 4 6 12 24 25 26 27 28…”
Section: Discussionmentioning
confidence: 99%
“…10 The diagnosis and treatment of acute intussusception is mainly air enema, which is not only the diagnostic method of acute intussusception, but also the first choice of treatment for acute intussusception. [11][12][13] It was reported that the success rate of air enema treatment of acute intussusception can be 90%. 14 The pressure of the air enema is generally maintained at 6~13kpa.…”
Section: Discussionmentioning
confidence: 99%